Republic of Guatemala Country Environmental Analysis : Addressing the Environmental Aspects of Trade and Infrastructure Expansion - World Bank (World Bank, Washington, DC, 2020)
Since the signing of the Peace Accords in 1996, Guatemala has made substantial progress in consolidating peace and democracy. While progress in socioeconomic development has been uneven, there have been important gains in education and health coverage, sustained increases in social sector spending, improved coverage of basic utility services, and better management of public finances, among other gains. Unfortunately, progress has been slower than expected in several important areas, including economic growth rates. Based on the best regional and international practices, this report concludes that mainstreaming environmental considerations into sectoral policies rather than scaling-up the operations of environmental agencies is the best way to prepare Guatemalan institutions for current environmental challenges and those it will encounter in the future. The report also emphasizes the need to provide the right incentives to economic agents (e.g., promoting compliance through achievable requirements but with credible sanctions to violators, rather than trying to change behavior by threatening with criminal charges that are ultimately not enforced), and to engage civil society by improving information and participation mechanisms.